2016
DOI: 10.1007/s00383-016-3996-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of sternal curvature angle on patients with pectus excavatum

Abstract: The difference in sternal curvature as measured by the sternal curvature angle between the pectus excavatum and normal patients was statistically significant. Our data suggest that sternal depression evident in PE patients is not a simple linear depression of the sternum but due to curvature in the sternal body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Recent studies hypothesize that the inward deformation of the anterior thoracic in PE may happen due to the growth disturbance of the sternum [ 115 , 116 , 117 ]. Both Haje et al (1999, 2021) and Lee at al.…”
Section: The Anatomopathological and Biomechanical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies hypothesize that the inward deformation of the anterior thoracic in PE may happen due to the growth disturbance of the sternum [ 115 , 116 , 117 ]. Both Haje et al (1999, 2021) and Lee at al.…”
Section: The Anatomopathological and Biomechanical Perspectivesmentioning
confidence: 99%
“…Both Haje et al (1999, 2021) and Lee at al. (2017), assessed the shape of the sternum in patients with chest wall deformities versus normal [ 115 , 116 , 117 ]. They observed that the sternum in patients with PE reveal abnormal shape, posterior curvature, torsion, and sometimes relatively sudden angulation [ 117 ].…”
Section: The Anatomopathological and Biomechanical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation